ANALISIS KEWAJARAN DAN PENERIMAAN HARGA TIKET PENERBANGAN LION AIR - Wiyono & Dwi Hastjarja KB (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2012)
ABSTRACT The purpose of research: 1) To know Price Fairness of influence to Customer Satisfaction; 2) To know the role of customer satisfaction and price fairness of the effect to customer loyalty; 3) To know the role of customer satisfaction and customer loyalty of the mediating of the effect price fairness to price acceptance. Data was obtained 150 customer Lion Air in Surakarta. The data was analyzed by Structural Equation Modelling (SEM), The result is: 1) Price fairness is positive significantly influence to Customer Satisfaction; 2) Prive fairness and Customer Satisfaction is positive significantly influence to Customer Loyalty; 3) Customer Satisfaction and Customer Loyalty is positive significantly influence to Price Acceptance.   Keywords: Price Fairness, Customer Satisfaction, Customer loyalty and Price Acceptance.